Does Employee Stock Ownership Work? Evidence from Publicly-Traded Firms in Japan - Takao Kato; Hideaki Miyajima; Hideo Owan (Institute of Labor Economics (IZA), 2018)
This paper provides novel evidence on the effects of employee stock ownership (ESO), a prominent example of shared capitalism. In so doing, we take advantage of our access to new panel data on Japanese ESO plans for a highly representative sample of publicly-traded firms in Japan (covering more than 75% of all firms listed on Tokyo Stock Exchange) over 1989-2013. Unlike most prior studies, we focus on the effects of changes in varying attributes of existing ESO – the effects on the intensive margin. Our fixed effect estimates show that an increase in the strength of the existing ESO plans measured by stake per employee results in statistically significant productivity gains. Furthermore, such productivity gains are found to lead to profitability gains since wage gains from ESO plans are statistically significant yet rather modest. Our analysis of Tobin's Q suggests that the market tends to view such gains from ESO plans as permanent. We further find that increasing the stake of the existing core participants is more effective in boosting gains from ESO plans than bringing in more employees into the trust. We use unique instruments (the peer firm's matching grant rate and abnormal return) to account for possible endogeneity of our ESO variables, and show that the estimated positive gains from ESO plans are not biased upward and likely to be lower bounds. We also find evidence for complementarity between ESO plans aimed at incentivizing non-executive employees and stock option aimed at incentivizing executives. Finally the positive effects on productivity, profitability, wages and Tobin's Q are found to be larger when the proportion of powerful institutional investors and foreign investors are greater; and smaller for larger firms that are more subject to the free-rider problem.
Keywords: J54; M52; G32; 330; employee stock ownership; shared capitalism; group incentive; productivity; Tobin's Q; managerial entrenchment